9S binding protein for androgens and progesterone. - Wilson, E M (1977)
A steroid binding protein fraction with a sedimentation coefficient of approximately 9 S (molecular weight approximately equal to 200,000) has been identified in 105,000 X g supernatants of several androgen-responsive organs. Highest concentrations were found in epididymis and testis, but small amounts were detected in prostate, seminal vesicle, kidney, submandibular gland, and lung. The 9S protein binds [3H]dihydrotestosterone (17beta-hydroxy-5alpha-androstan-3-one) and [3H]progesterone (4-pregnene-3,20-dione) with equilibrium binding constants of approximately 10(5) M-1 and 10(6) M-1, respectively. The concentration of 9S binding sites in epididymis is approximately 10(-11) mol/mg of supernatant protein, which is at least 10(5) times greater than the concentration of androgen receptor. 9S binding protein appears to be a nonsecretory, intracellular protein and has properties different from the andorgen receptor. It is unretarded on DEAE-Sephadex chromatography at pH 8.0, and its sedimentation rate on sucrose gradients is not altered at high ionic strength (0.4 M KCl). Like the androgen receptor, its binding activity, which is maximal between pH 7 and 9.5, is heat labile, decreased by sulfhydryl reagents, and enhanced by 2-mercaptoethanol. It is suggested that because of its high concentration and low affinity, 9S binding protein may function in the intracellular accumulation of compartmentalization of androgens or progesterone.